Inflammatory and neutrophil extracellular trap markers to predict cardiac events after ST-segment elevation myocardial infarction - Ana Blasco; Axel Rosell; Raquel Castejón; Ana Royuela; Charlotte Thålin; Elvira Ramil; Silvia Elorza; María-José Coronado; Paloma Martín; Javier Vázquez; Carolina González-Andrés; Juan M. Escudier; et al. (PLoS ONE, 2025)
Background and aims Inflammation plays a pivotal role in the pathophysiology of ST-elevation myocardial infarction (STEMI). This involves neutrophil activation and the local release of pro-inflammatory mediators. The formation of neutrophil extracellular traps (NETs) in coronary thrombosis has been linked to poor short-term prognosis following STEMI, but the usefulness of specific circulating NET components as prognostic markers is unclear. We aimed to evaluate the NET-specific marker nucleosomal citrullinated histone H3 (H3Cit-DNA) and other classical inflammatory markers to predict adverse events after STEMI. Methods This is a single-center retrospective cohort study of patients with STEMI undergoing primary percutaneous coronary intervention (PCI) from 2015 to 2019. We analyzed the association between serum H3Cit-DNA levels, double-stranded DNA, and classical inflammatory markers –such us interleukin (IL) 6 and 1β, TNF-α, and C-reactive protein (CRP)– on admission and the occurrence of major cardiovascular events (MACE), including death, reinfarction, urgent revascularization, or heart failure, after STEMI. Results A total of 487 patients were studied, of which 380 were men [78%]; mean [SD] age of patients was 63 [13] years, and median [95%CI] follow-up was 5.4 [5.2-5.5] years. Median [IQR] H3Cit level was 179.30 [105.30-281.47] ng/ml. No relevant association was found between H3Cit-DNA levels and 30-day mortality (OR, 1.03 [95%CI, 0.71-1.50], p = 0.861) or MACE (0.98 [0.72-1.32], p = 0.879), Killip class (0.95 [0.74-1.21], p = 0.664), or left ventricular ejection fraction (ref.cat. > 50%; < 35%, RRR 1.01 [95%CI, 0.74-1.38], p = 0.952; 35-50%, 1.26 [1.07-1.48], p = 0.005]. Adding CRP and IL-6 levels as covariates to a model based on classical risk factors significantly improved the prediction of MACE at 30 days after STEMI (IDI 0.13; NRI 0.32, p < 0.05). Conclusions Circulating levels of the NET marker H3Cit-DNA at the time of primary PCI were not predictive of cardiovascular events following STEMI. In contrast, the classical inflammatory markers CRP and interleukin-6 significantly enhanced the discriminative capacity of a clinical 30-day risk prediction model. These findings suggest that measuring circulating NET-specific markers may have limited utility in assessing the inflammatory state during the early stages of STEMI.